The Impact of the Modern Trends on the Complexing of the Business Model of High Tech IT Company - Denis S. Pashchenko (Methods in Science and Technology Studies, 2026)
This article explores the critical transformation of IT firms into high-tech companies (HTC) amid rapidly evolving industry trends, including sector-wide digitalization, the shift toward full virtualization of production processes, and the increasing integration of artificial intelligence (AI) tools in software engineering. These trends are fundamentally reshaping the competitive landscape, necessitating a proactive response from IT companies seeking to maintain and enhance their market positions. The article introduces an innovative model for high-tech companies, placing the production function at the core of a company’s competitive strategy. This model emphasizes the need for companies to adopt digitalized, automated processes across all phases of the software lifecycle, fully embrace remote and hybrid work models, and develop unique products driven by digital management systems. Additionally, the article presents a comprehensive set of strategic elements and tactical steps that IT companies can implement to achieve HTC status. These include fully virtualized production functions, geographically distributed teams that enable continuous product support and development, and the deployment of AI tools to enhance operational decision-making, sales forecasting, and customer support. A key focus is on maximizing value creation from intellectual property rather than traditional revenue streams such as outsourced software development or service provision. The study also highlights the need for companies to integrate predictive models and AI tools in various business areas, including marketing, sales, and product management, to strengthen their market position.